Effectiveness of Mentessori Multiplication Board Learning Media to Improve the Ability to Multiplicate 1-10 for Cerebral Palsy Children - Nadya Nurhasanah; Nurhastuti Nurhastuti; Mega Iswari; Damri Damri (Edumaspul: Jurnal Pendidikan, 2024)
This research was motivated by problems that researchers found at SLB N 1 Lima Kaum. A Cerebral Palsy student who is still not optimal in multiplication 1-10. This research aims to improve the ability to multiply numbers 1-10 using the Mentessori Multiplication Board learning media. Researchers use quantitative research with an experimental approach in the form of Single Subject Research (SSR). With A-B-A design. Data was analyzed using graphic visual analysis. Techniques for collecting data include tests and data collection tools for test questions. The subjects of the research were Cerebral Palsy students in class VIII SLB N 1 Lima Kaum. The research results show that the Mentessori multiplication board learning media is effectively used to improve the ability to multiply 1-10.